A review of biomass gasification systems for energy generation in Costa Rica between 1982 and 2014 - Castillo-Benavides, José Alberto (2018)
The development of the gasification in Costa Rica starts back in the 80s with the establishment of a gasification course arranged by the Latin American Organization of Energy (OLADE, by its Spanish acronym). Historically, the most commonly used biomass fuel for this process is wood waste, especially wood chips under 4 inches of length. In very few occasions, the use of other biomass fuels has been either implemented or studied in systems of gasification across the country. Due to the old age and the rudimentary character of the projects, the documentation and information related to them is rather scarce. The main experiences with gasification utilizing coffee bean skins as fuel, are from the Coffee Processing Plants of CoopeDota R.L. and CoopeTarrazú R.L. both plants developed this technology with very modest results due to the process unsteadiness, the generation of undesired compounds as tars and the emission of volatile organic compounds. On the other hand, there have been positive experiences with the gasification of the coffee husk. This material has simplified the design of gasifiers, given its low humidity content and particle size. Currently, the plants Cerro Los Vindas and Monte Rosa have both active coffee tusk gasifiers. From this review, the necessity of an in-depth examination of the physicochemical properties of the coffee skin becomes clear, as well as the evaluation of the thermodynamic behavior of the gasification process when using this biomass waste as fuel.